Corporate governance, accounting regulation, and financial reporting quality of listed firms in Nigeria - Jehu, Philip (2019)
The purpose of this study is to examine the relationship between corporate governance, accounting regulation, and financial reporting quality (FRQ) of listed firms in Nigeria. Specifically, this thesis examines whether: 1) board characteristics (BC), 2) audit committee (AC) attributes, and 3) accounting regulation are associated with FRQ, and 4) accounting regulation moderates the relationship between the explanatory variables and FRQ. Using 96 samples of 768 firm-year observations for the period 2009 - 2016, the study utilised the panel data analyses by employing the Panel Corrected Standard Errors estimator. This study finds the following predictors to be significant in improving FRQ: board size and boards comprising a larger proportion of nonexecutive directors. Further, CEO gender effectively improves FRQ, hence creating visibility for affirmative action. Longer CEO tenure enhances FRQ, and accounting regulation effectively reduces abnormal accruals, which in turn improves FRQ. However, this study finds no cause to associate the proportion of independent nonexecutive directors, gender diversity, ethnic diversity, educational qualification, board meetings, AC independence, AC financial expertise, AC size, and AC meeting with FRQ. Because of inconsistent findings, the study introduced a moderator to enhance the relationship between all the explanatory variables and the dependent variable. The results show that FRQ is significantly improved by CEO gender, CEO tenure, and ethnic diversity, but board size and the proportion of non-executive directors turned insignificant. Likewise, the proportion of independent non-executive directors, gender diversity, educational qualification, board meetings, AC independence, AC financial expertise, AC size, and AC meeting all maintained insignificant outcomes. This study theoretically and practically contributes mainly to the agency theory by adding insight to the regulatory and governance dynamics of the board and AC size, composition, diligence, and independence. Further studies could investigate more corporate governance constructs and their effect on FRQ.